2021
DOI: 10.3390/cancers13194983
|View full text |Cite
|
Sign up to set email alerts
|

Mir-21 Suppression Promotes Mouse Hepatocarcinogenesis

Abstract: The microRNA 21 (miR-21) is upregulated in almost all known human cancers and is considered a highly potent oncogene and potential therapeutic target for cancer treatment. In the liver, miR-21 was reported to promote hepatic steatosis and inflammation, but whether miR-21 also drives hepatocarcinogenesis remains poorly investigated in vivo. Here we show using both carcinogen (Diethylnitrosamine, DEN) or genetically (PTEN deficiency)-induced mouse models of hepatocellular carcinoma (HCC), total or hepatocyte-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…In agreement, our data indicate that TIA1 loss is associated with an increase in several secreted factors (e.g., S100 family members, osteopontin), which could potentially foster HCC development by promoting inflammation, hepatic fibrosis, and immune escape of cancer cells, as previously demonstrated [ 4 ]. Further illustrating discrepant data arising from in vivo versus in vitro experimental settings, we previously reported that another AUBP tristetraprolin (TTP), or miRNAs such as miR-21, also display opposite functions in vitro versus in vivo in cancer-related processes [ 10 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement, our data indicate that TIA1 loss is associated with an increase in several secreted factors (e.g., S100 family members, osteopontin), which could potentially foster HCC development by promoting inflammation, hepatic fibrosis, and immune escape of cancer cells, as previously demonstrated [ 4 ]. Further illustrating discrepant data arising from in vivo versus in vitro experimental settings, we previously reported that another AUBP tristetraprolin (TTP), or miRNAs such as miR-21, also display opposite functions in vitro versus in vivo in cancer-related processes [ 10 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCC development is tightly associated with the deregulated activity of various AUBPs, e.g., HuR [ 8 ] or T-cell-restricted intracellular antigen-1 (TIA1) [ 9 ]. Moreover, our previous work has uncovered other AUBPs deregulated in human HCC [ 10 ]. This study identifies TIA1 as a potential TS, whose function in HCC remains poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-21 downregulation is associated with the progression of the disease from NASH to HCC, as was demonstrated in animal and human HCC models [ 82 ]. The aforementioned phenomenon is attributed to the disruption of several signaling pathways, such as STAT3, AKT/PKB, and TGF-b [ 83 ].…”
Section: The Emerging Role Of Mirnas In Hccmentioning
confidence: 98%
“…Targeting delivery of therapeutic miR-21 has been reported to improve the recovery of cardiac function after myocardial infarction [ 53 ]. However, miR-21 is also overexpressed in a variety of diseases, including cancer, so it is also regarded as an oncomiR [ 54 ]. miR-34, as an aging-related miRNA, is related to cardiac dysfunction and related cardiovascular diseases.…”
Section: Mirnas: Regulatory Factors Of the Heartmentioning
confidence: 99%